The 'Celtic crisis': Guarantees, transparency and systemic liquidity risk - Philipp König; Kartik Anand; Frank Heinemann (Bank of Canada, 2013)
Bank liability guarantee schemes have traditionally been viewed as costless measures to shore up investor confidence and prevent bank runs. However, as the experiences of some European countries, most notably Ireland, have demonstrated, the credibility and effectiveness of these guarantees are crucially intertwined with the sovereign's funding risks. Employing methods from the literature on global games, we develop a simple model to explore the systemic linkage between the rollover risks of a bank and a government, which are connected through the government's guarantee of bank liabilities. We show the existence and uniqueness of the joint equilibrium and derive its comparative static properties. In solving for the optimal guarantee numerically, we show how its credibility can be improved through policies that promote balance-sheet transparency. We explain the asymmetry in risk transfer between the sovereign and the banking sector, following the introduction of a guarantee as being attributed to the resolution of strategic uncertainties held by bank depositors and the opacity of the banks' balance sheets.
Keywords: G01; G28; D89; 330; Financial stability; Financial system regulation and policies